Perfluoroalkyl substances and likelihood of stroke in persons with and without diabetes. (January 2020) - Hutcheson, Robert; Innes, Kim; Conway, Baqiyyah
Objective: The main objective of this study is to evaluate the relationship of perfluoroalkyl substances with stroke and any modifying influence of diabetes. Methods: Data on 3921 adults aged ⩾20 years with and 44, 285 without diabetes were drawn from the C8 Health Project. Four perfluoroalkyl substances were investigated: perfluorohexane sulphate, C8 – perfluorooctanoic acid, perfluoroctane sulfonate and perfluorononaoic acid. Results: There were 238 cases of stroke among those with and 643 among those without diabetes. In analyses controlled for age, sex, race, diabetes duration, body mass index, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, C-reactive protein, kidney function and a history of smoking, a history of stroke was significantly inversely associated with serum perfluorohexane sulphate (odds ratio = 0.75, 0.64–0.88) and perfluoroctane sulfonate (odds ratio = 0.81, 0.70–0.90), but not perfluorooctanoic acid (odds ratio = 1.04, 0.94–1.15) or perfluorononaoic acid (odds ratio = 0.89, 0.70–1.14) among those with diabetes. Perfluoroalkyl substances demonstrated no association with stroke among those without diabetes ( p interaction = 0.006 and 0.01 for perfluorohexane sulphate and perfluorooctanoic acid, respectively). Conclusion: In this large cross-sectional study, serum levels of perfluorohexane sulphate and perfluoroctane sulfonate were inversely associated with stroke among those with diabetes. Although mechanisms and implications for this diabetes-specific inverse relationship need to be further explored, our data suggest that perfluoroalkyl substances do not increase risk of stroke among persons with or without diabetes.